Use of Therapeutic Hypothermia in Sudden Unexpected Postnatal Collapse: A Retrospective Study - Brito, Sara (2021)
Introduction: Sudden and unexpected postnatal collapse is a rare event with potentially dramatic consequences. Intervention approaches are limited, but hypothermia has been considered after postnatal collapse. The aim of this study was to analyse sudden and unexpected postnatal collapse cases that underwent therapeutic hypothermia in the five Portuguese hypothermia centres.Material and Methods: In this multicentre, retrospective and descriptive study, clinical, ultrasonography, amplitude-integrated electroencephalography and brain magnetic resonance findings of newborns with postnatal collapse that underwent therapeutic hypothermia are reported (2010 - 2018). Statistical analysis was performed by using IBM SPSS Statistics version 21.Results: Twenty-two cases of sudden and unexpected postnatal collapse were referred for therapeutic hypothermia (82% outborn), all ≥ 36 weeks, with Apgar 5´ ≥ 8. Collapse occurred during the first two hours in 73% (all < 24 hours), 50% during skin-to-skin care, 55% related to feeding and 23% during co-bedding. Moderate-severe encephalopathy and severe acidosis were observed (median: Thompson score 16, pH 6.90, base deficit 22 mmol/L). Amplitude-integrated electroencephalogram was abnormal in 95% and magnetic resonance imaging showed severe brain injury in 46%. The mortality rate was 50%. A possible cause was identified in 27%.Discussion: The incidence rate of 2.7 sudden cases of postnatal collapse per 100 000 births, is possibly under-estimated. All infants suffered the collapse in the first day, mostly within the first two hours, as reported before. Possible causes were identified in less than a third of cases, but multiple predisposing conditions were identified, suggesting that prevention may be possible. Newborn positioning and skin-to-skin care have been the most discussed practices. A significant proportion of infants had poor outcomes. Lower Thompson score, electroencephalogram amplitude normalization and normal magnetic resonance imaging seemed to indicate better outcomes. Although conclusive trials on therapeutic hypothermia after postnatal collapse are not available, its use has been considered individually. No severe adverse effects directly related to hypothermia were registered in this study, but the results do not allow drawing meaningful conclusions.Conclusion: In our national sample of 22 infants who suffered sudden and unexpected postnatal collapse and underwent therapeutic hypothermia, a significant proportion had poor outcomes. Absolute conclusions from our experience with hypothermia in postnatal collapse cannot be drawn, but systematic reporting of cases and long-term clinical evaluation would facilitate understanding of the real benefits of hypothermia. As this procedure has not been validated with clinical trials for this indication, its use should be considered on a case-by-case approach. The potentially avoidable nature of unexpected postnatal collapse is evident from its association with certain behaviours and risk factors. Surveillance practices during the first hours should be implemented, whilst the benefits of breastfeeding and skin-to-skin care should continue to be widely promoted.